RANKING RUSSIAN UNIVERSITIES: HOW TO MEASURE? - Maria V. Seroshtan; Boris M. Vladimirskiy (Moscow Polytechnic University, 2016)
The authors propose to use vector representation of university areas of activities for ranking universities. Two novel indices reflecting UN experts' recommendations are introduced. Based on expert estimates, a priority vector of weights enables to represent the university activity.